Defective MOFs-based electrocatalytic self-cleaning membrane for wastewater reclamation: Enhanced antibiotics removal, membrane fouling control and mechanisms. (15th July 2022) - Zhou, Shihao; Zhu, Junwen; Wang, Zunrui; Yang, Zhen; Yang, Weiben; Yin, Zhonglong
Highlights: Defective UiO-66 based UF anodic membrane was fabricated for water reclamation. The fabricated membrane has superior antibiotic removal and self-cleaning property. New insights into the self-cleaning mechanism of anodic membrane were proposed. The excellent electrochemical stability ensured the long-term membrane operation. Abstract: In order to resolve the poor antibiotics rejection and serious fouling of ultrafiltration (UF) membrane during municipal wastewater reclamation, a novel anodic membrane (defective UiO-66 (D-UiO-66)/Graphite/Polyvinylidene fluoride (PVDF)) with high pure water flux (596.1 L h   −   1 m   −   2 bar −1 ) was fabricated by incorporating defective zirconium based metal-organic framework (D-UiO-66) and conductive graphite particles into PVDF matrix and applied in the coupling of electro-oxidation and membrane filtration process. Compared to the other anodic membranes (i.e., Graphite/PVDF and UiO-66/Graphite/PVDF), D-UiO-66/Graphite/PVDF possesses superior anti-fouling and self-cleaning abilities (flux recovery=100%, model foulant: bovine serum albumin) in both intermittent and continuous supply of electric field under current density of 0.01 mA/cm 2 ; moreover, efficient antibiotics (tetracycline, norfloxacin, tylosin and sulfamethoxazole) removal (> 96.6%) and bactericidal efficiency against E. coli and S. aureus (100%) were achieved simultaneously without the addition of chemical reagents due to the higher electrocatalytic activity of anodic membrane for oxidation of pollutants by OH and O2 – free radicals. Three degradation pathways of antibiotics were proposed and the self-cleaning mechanism of membrane was dominated by the synergy of the partial mineralization and the reduced fouling potential of foulants after oxidation as revealed by the increase in hydrophilicity, and decrease in negative charge and molecular weight. The fabricated membrane also presents excellent electrochemical stability, separation and self-cleaning performance for treatment of municipal secondary effluent during long-term filtration with low electric energy consumption, which is promising in wastewater reclamation. Graphical abstract: Image, graphical abstract